2002
DOI: 10.1002/ajh.10117
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of β‐thalassemia mutations and their association with allelic sequence polymorphisms at the β‐globin gene cluster in an eastern Indian population

Abstract: In this report, the spectrum of ␤-thalassemia mutations and genotype-to-phenotype correlations were defined in large number of patients (␤-thalassemia carriers and major) with varying disease severity in an Eastern Indian population mainly from the state of West Bengal. The five most common ␤-thalassemia mutations were detected, which included IVS1-5 (G➝C), codon 15 (G➝A), codon 26 (G➝A), codon 30 (G➝C), and codon 41/42 (−TCTT). These accounted for 85% in 80 ␤-thalassemic alleles deciphered from 56 patients, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 28 publications
2
14
0
Order By: Relevance
“…Our results are in concordance of Kukreti, et al (2002) found association with (AT) 8 (T) 5 motif. We also found that 8 (T) 5 motif at a frequency of 28/40 (70%), (AT) 9 (T) 5 4/40 (10%) and (AT) 7 (T) 7 8/40 (20%).…”
Section: Other Articlesupporting
confidence: 92%
See 1 more Smart Citation
“…Our results are in concordance of Kukreti, et al (2002) found association with (AT) 8 (T) 5 motif. We also found that 8 (T) 5 motif at a frequency of 28/40 (70%), (AT) 9 (T) 5 4/40 (10%) and (AT) 7 (T) 7 8/40 (20%).…”
Section: Other Articlesupporting
confidence: 92%
“…motif like (AT) 8 (T) 5 , (AT) 7 (T) 7 , (AT) 9 (T) 5 prevalent among thalassemia chromosomes. The (AT) 7 (T) 7 motif seemed only [6]. Bandyopadhyay, et al (2005) [7] reported 65% prevalence of this motif in East India normal population.…”
Section: Other Articlementioning
confidence: 96%
“…Interestingly, all β thalassemia chromosomes carrying the Codon 15 (G→A) mutation showed the presence of (AT) 9 (T) 5 allele. A study in Eastern Indian population had shown the linkage of known β thalassemia mutations with the (AT) 8 (T) 5 configuration 22. Goncalves et al (1998) reported that presence of both the (AT) 9 (T) 5 sequence configuration at position −530 of the β globin gene and a (C→T) variation at −158 of the G γ globin gene is associated with elevated expression of HbF.…”
Section: Discussionmentioning
confidence: 99%
“…With the advent of polymerase-chain reaction technique [PCR], some of the VNTR loci like D1S80, APOB, and YNZ22 have been analysed and data are now available for population and forensic studies. Some studies have been carried out on the distribution and variation of VNTR loci among the central, western and eastern Indian populations (Papiha et al 1996, Mastana, 1999, Mastana et al 2000, Mastana and Papiha, 2001, Das et al 2002, Das and Mastana, 2003.…”
Section: Single Nucleotide Polymorphisms and Restriction Fragment Lenmentioning
confidence: 99%
“…These include Brahmin, Khatri, Dhimer caste groups and Baiga and Gond tribes from Madhya Pradesh, Gadaba, Kuvi-khond, Paroja tribes from Orissa, Thoti and Kolam tribes from Andhra Pradesh. The data from this study (Mastana and Papiha, 2001) combined with other published data on Konkanastha and Maratha from Maharashtra (Das et al 2002) allow calculation of the genetic distances (DA). A UPGMA dendrogram from this analysis [ Figure 3-3] suggests that most of the populations are geographically aligned and correspond to their social/tribal status.…”
Section: Single Nucleotide Polymorphisms and Restriction Fragment Lenmentioning
confidence: 99%